202k views
2 votes
The inverse equation

The inverse equation-example-1

2 Answers

4 votes

Answer:

The inverse is (x-1)^5 +2

Explanation:

y = 1 + (x-2) ^ 1/5

Exchange x and y

x = 1 + (y-2) ^ 1/5

Solve for y

Subtract 1 from each side

x-1 = 1-1 +(y-2) ^ 1/5

x-1 = (y-2) ^ 1/5

Raise each side to the 5th power

(x-1) ^5 = (y-2) ^ 1/5^5

(x-1)^5 = y-2

Add 2 to each side

(x-1)^5 +2= y-2+2

(x-1)^5 +2= y

The inverse is (x-1)^5 +2

User Mymmaster
by
6.1k points
3 votes

Answer:

y = (x-2)⁵+2

Explanation:

y = 1 +
\sqrt[5]{x-2}

inverse is switching x and y

x = 1+
\sqrt[5]{y-2}

x-1 =
\sqrt[5]{y-2}

(x-1)⁵= y-2

y = (x-1)⁵+2

User Mats Lind
by
6.0k points